Spectrophotometric Methods for the Estimation of Meloxicam in Dosage Forms - Basu, S.K.; Mandal, Sanchita (Asian Journal of Chemistry, 2010)
For the estimation of meloxicam from dosage forms two simple, quick, sensitive, visible and UV spectrophotometric methods were developed. The visible method is based on the formation of an intense brownish green coloured complex with ferric ammonium sulfate, which was stable at room temperature. The coloured product is quantitated spectrophotometrically at 396 nm and was found to obey the Beer's law in the concentration range of 5-30 μg mL-1. The UV method is based on the ionization of meloxicam and the maximum absorption was found at 354 nm and obeyed the Beer's law in the concentration range of 3-12 μg mL-1. The methods were applied for estimation of different meloxicam tablets with mean percentage accuracies of 99.28 ± 0.2802, 99.28 ± 0.1997 and 99.81 ± 0.6040, respectively with visible spectrophotometric method and 99.47 ± 0.5297, 99.73 ± 0.1300 and 98.91 ± 0.6810, respectively with UV spectrometric method.